2016
DOI: 10.1016/j.ymben.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimal tracers for parallel labeling experiments and 13C metabolic flux analysis: A new precision and synergy scoring system

Abstract: 13C-Metabolic flux analysis (13C-MFA) is a widely used approach in metabolic engineering for quantifying intracellular metabolic fluxes. The precision of fluxes determined by 13C-MFA depends largely on the choice of isotopic tracers and the specific set of labeling measurements. A recent advance in the field is the use of parallel labeling experiments for improved flux precision and accuracy. However, as of today, no systemic methods exist for identifying optimal tracers for parallel labeling experiments. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 45 publications
0
54
0
Order By: Relevance
“…Because different tracers provide varying degrees of relative flux information (see Fig. 5), the integrated analysis of several tracer experiments can have an additive impact on flux resolution and result in highly precise relative flux estimates (24). The experimental design from Khairallah et al (32) was aptly suited for the application of integrated flux analysis with parallel labeling experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because different tracers provide varying degrees of relative flux information (see Fig. 5), the integrated analysis of several tracer experiments can have an additive impact on flux resolution and result in highly precise relative flux estimates (24). The experimental design from Khairallah et al (32) was aptly suited for the application of integrated flux analysis with parallel labeling experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In studies with multiple animal treatment groups, parallel tracer labeling approaches may not be practical depending on the number of tracers interrogated and the amount of biological replicates required. In efforts to reduce the amount of perfusions required for 13 C-MFA, mixtures of tracers may be the best option for elucidating TCA cycle fluxes in the perfused heart; however, it is likely that this will incur a cost of decreased flux resolution as shown with previous studies (21,24). These aforementioned challenges present interesting questions for the future direction of 13 C-MFA in perfusion studies and warrant further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crown et al identified [3,4- 13 C]- and [2,3,4,5,6- 13 C]-labeled glucose to be favorable for elucidating reaction rates in the oxidative pentose phosphate pathway (PPP) and pyruvate carboxylase flux, respectively, based on a small scale network with two free fluxes [35]. Later on, the same group determined [1,2- 13 C]-, [5,6- 13 C]-, and [1,6- 13 C]-labeled glucose as best single tracers for Escherichia coli wild type [36]. A study of Metallo et al suggested [1,2- 13 C]-labeled glucose to be the optimal commercial tracer for most fluxes in the PPP and glycolysis in lung carcinoma cell lines while uniformly labeled glutamine provided optimal results for tricarboxylic acid cycle (TCA) fluxes [37].…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Tracer choice directly impacts the isotopologues and fluxes that can be determined from a particular experiment, and computational approaches have been developed to evaluate, optimize, and design tracer combinations with enhanced resolution [4850]. For example, combinations of glucose tracers are useful for studying the pentose phosphate pathway [51], and glutamine tracers are particularly informative when studying tricarboxylic acid (TCA) metabolism in proliferating cancer cells [48].…”
Section: Technological Advances In Studying Metabolismmentioning
confidence: 99%